Understanding round-tripping phenomenon in Russian context – case Cyprus - Nuotio, Jaakko (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2016)
Russian FDI has a few peculiarities. One of them is round-tripping. Round-tripping is defined as transfer of funds abroad, usually to offshore financial centers (OFCs), and then bringing all or some of the investment back as foreign investment. Russian context was chosen for this study because the share of round-tripping investments from country’s total FDI is extensive. However, it needs to be addressed that this is not just a Russian phenomenon. Round-tripping is used by many developed and developing countries, and most of the countries have their own designated destinations for this kind of capital, much like Cyprus is the main destination for Russian capital. It is important to study this phenomenon further, since it falsifies FDI statistics and can lead to poor decisions on state level. Theoretical part of the study tries to determine weather traditional FDI and internationalization theories fit to explain the Russian round-tripping phenomenon. Traditional FDI and internationalization theories are first introduced in general terms, and then further examined in Russian context. In traditional endogenic FDI theories, when the capital is formed in one country it goes abroad to find better profits. At a first glance, this seemed not to be the case in round-tripping. However, during the study it became rather clear that with few adjustments and changes in perspective, traditional theories could be used to explain round-tripping phenomenon. For example, OLI paradigm can be further developed into OLIH paradigm with ‘H’ representing the important home country institutions. Transaction based view and resource seeking theories were also seen well equipped to explain round-tripping with a change in perspective. The latter part of the study focused on holistic understanding of Russian –Cyprian investment relationship. Study aims to shed light into the determinants and consequences of this phenomenon for both countries involved. The two share historical, cultural and political ties, but most importantly common financial interests. Russian companies seek security and financial knowledge to maneuver their assets and Cyprian economy largely is dependent on their disproportionally large financial sector. Consequences for Cyprian economy were seen in current economic crisis, when the need for their financial services diminished. Russian government on the other hand is losing vast amounts of tax money due to this phenomenon. A rather extreme view was also introduced in this study. Round-tripping phenomenon and OFCs are an important reason why corruption exists, since if one does not have a way to make ill-gained money legitimate why try to ill-gain the money at the first place. The most important finding of the study is that round-tripping companies are in a better competitive position than genuine and purely domestic investor due to their institutional knowledge.